Experience of nursing resident students in coping with Covid-19 (Research, Society and Development, 2022)
Introduction: This study aimed to understand the feelings experienced by lato sensu graduate students, in the nursing residency modality, during the period in which they exercised their activities during the Covid-19 pandemic and the confrontation of the imposed social distance. Methodology: Descriptive study with a quantitative approach, 59 nursing graduate students participated in the research in the residence molds. Results: According to age, participants in the 20 to 30 age group were the ones who had the highest participation with 41 responses. The predominant complaint among the participants was physical fatigue and excessive sleep, with 78% and 48%, respectively. Another relevant data is that 14% of the participants started to use psychotropic drugs after the beginning of the pandemic. Despite the family support that residents received, 24% of respondents chose to move away from their families for fear of transmitting Covid-19 and 20% reported that they are questioned in their social cycle regarding their responsibility to be a vector of the disease, since they are in direct contact with it. Conclusion: The Covid-19 pandemic physically and mentally affected nursing residents so that they felt psychically shaken, unmotivated, tired and overwhelmed in the face of the scenario experienced. Social distancing and the absence of family contact also corroborated the emotional suffering, in many responses the residents showed lack of motivation to update themselves in the practices of coping with Covid-19 and the questions pertinent to the residence.